Father Involvement and Mother–Father Coordination as Predictors of Child Social Competence - Muñoz, Nayelli; Hernández, Carlos (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to examine the predictive roles of father involvement and mother–father coordination on child social competence in a sample of Mexican families.Methods: A correlational descriptive design was used to explore the relationships between father involvement, mother–father coordination, and social competence in children. The sample consisted of 432 parents from urban and semi-urban regions of Mexico, selected based on the Morgan and Krejcie sample size table. Standardized instruments were used to assess each variable: the Inventory of Father Involvement (IFI), the Coparenting Relationship Scale (CRS), and the Social Skills Rating System (SSRS). Data analysis was conducted using SPSS-27. Pearson correlation was used to evaluate the relationships between each independent variable and the dependent variable, and multiple linear regression was performed to determine the combined and unique predictive effects of the two independent variables on child social competence.Findings: Pearson correlation coefficients revealed that father involvement (r = .43, p < .01) and mother–father coordination (r = .47, p < .01) were both significantly and positively associated with child social competence. The multiple linear regression model was statistically significant (F(2, 429) = 61.42, p < .01), with an R² of .34, indicating that 34% of the variance in social competence was explained by the predictors. Both father involvement (B = 0.06, β = .25, p < .01) and mother–father coordination (B = 0.08, β = .31, p < .01) made significant unique contributions to the model.Conclusion: The findings highlight the critical roles of both direct paternal engagement and coordinated coparenting in fostering children’s social competence. Interventions aiming to enhance children’s social skills should incorporate strategies that support father involvement and strengthen collaborative parenting dynamics.